Компенсація реактивної потужності засобами синхронного електропривода - Сінолиций, Анатолій Пилипович; Кольсун, В'ячеслав Анатолійович; Кальмус, Дмитро Олегович; Жуйков, Микола Володимирович (НТУ "ХПІ", 2010)
The article considers subjects of energy efficiency enhancement in supply systems with synchronous machines. The work concentrates attention on reactive power compensation by means properties of synchronous machines. It is shown that the developed system keep the level of reactive on adjusted level.
Compensation of reactive power by means of synchronous electrical driver
Keywords: електропостачання; система регулювання; обмотка статора; навантаження; потужність